Quantitative evaluation of the actual hydrogen atom donating activities of O–H bonds in phenols: structure–activity relationship. Issue 5 (23rd January 2023) - Fu, Yan-Hua; Zhang, Yanwei; Wang, Fang; Zhao, Ling; Shen, Guang-Bin; Zhu, Xiao-Qing
Abstract : The H-donating activity of phenol and the H-abstraction activity of phenol radicals have been extensively studied. Abstract : The H-donating activity of phenol and the H-abstraction activity of phenol radicals have been extensively studied. In this article, the second-order rate constants of 25 hydrogen atom transfer (HAT) reactions between phenols and PINO and DPPH radicals in acetonitrile at 298 K were studied. Thermo-kinetic parameters Δ G ≠o (XH) were obtained using a kinetic equation [Δ G ≠XH/Y = Δ G ≠o (XH) + Δ G ≠o (Y)]. Bond dissociation free energies Δ G o (XH) were calculated by the iBonD HM method, whose details are available at ; https://pka.luoszgroup.com/bde_prediction . Intrinsic resistance energies Δ G ≠XH/X and Δ G ≠o (X) were determined as Δ G ≠o (XH) and Δ G o (XH) were available. Δ G o (XH), Δ G ≠XH/X, Δ G ≠o (XH) and Δ G ≠o (X) were used to assess the H-donating abilities of the studied phenols and the H-abstraction abilities of phenol radicals in thermodynamics, kinetics and actual HAT reactions. The effect of structures on these four parameters was discussed. The reliabilities of Δ G ≠o (XH) and Δ G ≠o (X) were examined. The difference between the method of determining Δ G ≠XH/X mentioned in this study and the dynamic nuclear magnetic method mentioned in the literature was studied. Via this study, not only Δ G o (XH), Δ G ≠XH/X, Δ G ≠o (XH) and Δ G ≠o (X) of phenols could be quantitatively evaluated, but also the structure–activity relationship of phenols is clearly demonstrated. Moreover, it lays the foundation for designing and synthesizing more antioxidants and radicals.